2012
DOI: 10.20460/jgsm.2012615784
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of End User Perceptions of Information Technologi̇es on the Informati̇on Sharing

Abstract: In recent decades, extant studies have focused on dominance of Information Technologies (IT) using different perspectives. While some of these studies utilized domains of IT management, remaining scholarly works dealt with issues of employee perceptions regarding IT usage and how IT usage affects employee outcomes such as job satisfaction. Accordingly, aim of this study is to explore and measure how IT related perceptions of employees determine the use and sharing of information they derive out of using the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In this study, US relates to the degree to which the users are satisfied with the IS. Several studies have pointed out that US has a significant positive relationship with the users' perception of IS success (Davis, 1989;Seddon, 1997;Hussein, 2009), and technology acceptance (King, 1999;Pinar and Erzengin, 2012). Therefore, this study proposes the following hypotheses: H12 US has a significant relationship with UP of the IS success.…”
Section: Ipc Factorsmentioning
confidence: 86%
See 2 more Smart Citations
“…In this study, US relates to the degree to which the users are satisfied with the IS. Several studies have pointed out that US has a significant positive relationship with the users' perception of IS success (Davis, 1989;Seddon, 1997;Hussein, 2009), and technology acceptance (King, 1999;Pinar and Erzengin, 2012). Therefore, this study proposes the following hypotheses: H12 US has a significant relationship with UP of the IS success.…”
Section: Ipc Factorsmentioning
confidence: 86%
“…Hence, success and failure could be seen from the user's perspectives (Dwivedi et al, 2014). Little attention has been paid to the users' perceptions of the IS success, despite their potential impact on the productivity and effectiveness of organisations (Pinar and Erzengin, 2012). In addition to ISS, the users are also one of the key factors in the failure of an IS usefulness and satisfaction (Khosravi, 2013;Me, 2014;Udo and Guimaraes, 1994).…”
Section: Up Of Is Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, success and failure could be seen from the user's perspectives (Dwivedi et al, 2014). Little attention has been paid to the users' perceptions of the IS success, despite their potential impact on the productivity and effectiveness of organisations (Pinar and Erzengin, 2012). In addition to ISS, the users are also one of the key factors in the failure of an IS usefulness and satisfaction (Khosravi, 2013;Me, 2014;Udo and Guimaraes, 1994).…”
Section: Up Of Is Successmentioning
confidence: 99%
“…1 INTDB: refers to the extent to which different users depend on each other to accomplish their tasks (Barki and Hartwick, 2001 (Pinar and Erzengin, 2012;Al-Adaileh, 2009). Apart from that, prior studies have shown that PU has a positive relationship with US (Wang et al, 2010;Amin and Abolghasemi, 2014).…”
Section: Ipc Factorsmentioning
confidence: 99%